The theosophical enlightenment - Godwin, Joscelyn (State University of New York Press, 1994)
An enticing intellectual history of various esoteric currents from the early Romantic period to the early twentieth century. The author maintains that the Theosophical Society held a crucial position as the place where all those currents temporarily united, before diverging again.
Keywords: Theosophy -- Great Britain -- History.; Occultism -- Great Britain -- History.; Occultisme -- Grande-Bretagne -- Histoire.; Théosophie -- Grande-Bretagne -- Histoire.; RELIGION -- Eckankar.; BODY, MIND & SPIRIT -- New Thought.; Occultism; Theosophy; Great Britain; Geschichte; Okkultismus; Theosophie; Großbritannien; Theosofie.; Occultisme.; Geschichte -- 1800-1930; Occultism -- Great Britain -- History; Theosophy -- Great Britain -- History; History